2013
DOI: 10.1038/srep01044
|View full text |Cite
|
Sign up to set email alerts
|

Developmental processes in face perception

Abstract: Understanding the developmental origins of face recognition has been the goal of many studies of various approaches. Contributions of experience-expectant mechanisms (early component), like perceptual narrowing, and lifetime experience (late component) to face processing remain elusive. By investigating captive chimpanzees of varying age, a rare case of a species with lifelong exposure to non-conspecific faces at distinctive levels of experience, we can disentangle developmental components in face recognition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 44 publications
4
45
0
Order By: Relevance
“…More importantly, the FIE effect in the current study was selective for the face class which the perceptual systems of our participants was tuned to46, confirming our hypothesis (Figure 1b–e). In YC the FIE was more pronounced for chimpanzee than human faces, while in OC the FIE was more pronounced in human than chimpanzee faces.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…More importantly, the FIE effect in the current study was selective for the face class which the perceptual systems of our participants was tuned to46, confirming our hypothesis (Figure 1b–e). In YC the FIE was more pronounced for chimpanzee than human faces, while in OC the FIE was more pronounced in human than chimpanzee faces.…”
Section: Discussionsupporting
confidence: 89%
“…The participants were required to indicate which of the two pictures of the match-distractor pair displayed the same individual as the cue picture by touching it. Critical for our hypothesis is to replicate the modulation of correct responses for the two types of faces between age groups as shown in our previous study46, reflecting the specific tuning to one or the other face class: We therefore ran a mixed model ANOVA (with stimulus class and age group as fixed factors and participants as random factor nested in age group) and found a significant interaction between the factors age group and stimulus class (F(1,11) = 7.79, p < .05, mean square = .047) (Figure 1b, solid colors). There were no significant main effects for the factors age group (p = .96) and stimulus class (p = .51).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Meals included a wide variety of fresh fruits and vegetables fed throughout the day supplemented with nutritionally balanced biscuits (twice daily) and water available ad libitum. The chimpanzees have been familiar with humans since birth, interacting with them on a daily basis and have taken part in cognitive experiments including matching to sample tasks since youth (for example, see[1517, 39]. For the daily experiments, the chimpanzees left the group voluntarily on the request of experimenters, moved into the experimental booth, and moved back to the group after the completion of experiments (approx.…”
Section: Methodsmentioning
confidence: 99%
“…Conclusive evidence has shown that this effect is primarily due to a disruption in the processing of configural, rather than featural, information in faces [e.g., [913]. The face inversion effect has been observed in chimpanzees too, and although not all chimpanzees show this effect at all times[14, 15], overall there is evidence that configural processing is a critical element of efficient face detection in chimpanzees as well[16, 17]. Thus, effects of inversion have been observed for faces and whole bodies, but are generally not found for individual body parts[18].…”
Section: Introductionmentioning
confidence: 99%